La apatridia en Ecuador. Los efectos jurídicos de la carencia o pérdida de la nacionalidad - Zamora Andrade, María Fernanda (2014)
Nationality has traditionally been conceived as a legal and political bond between people and the state that generates reciprocal rights and obligations. This classic definition has been questioned because the state has the power to deprive people of their nationality internationally recognized as an essential human right to access and exercise of other rights such as identity, education, employment and health among others. As a result of this exclusive power of the State, there are millions of cases of stateless, that is; people who have not been recognized as nationals by any country and therefore are not considered subjects of rights and obligations. This research aims to analyze and highlight the causes and effects of a situation that affects people who do not have their right to nationality. According to UNHCR (United Nations High Commissioner for Refugees), there are approximately over 12 million stateless people in all regions of the world (ACNUR in Spanish). However, the magnitude of statelessness is not visible as in this figure there is no basis of records in each state nor international interest to channel this situation. Ecuador has also shown cases of people without nationality, either having not acquired from birth or having been deprived of it after its recognition. The main disadvantages faced by the country to recognize, prevent and eliminate cases of stateless come from the lack of specific legislation of statelessness as well as public institutions and policies that act against the circumstances giving rise to these cases.